2014
DOI: 10.1182/blood-2013-05-499707
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of the activating receptor NKG2D in natural killer cells is regulated by STAT3 tyrosine phosphorylation

Abstract: Signal transducer and activator of transcription 3 (STAT3) is considered a negative regulator of inflammation, as inhibition of STAT3 signaling enhances antitumor immunity. However, STAT3 activation is a key oncogenic pathway in natural killer (NK)-lineage large granular lymphomas, and we recently reported enhanced proliferation and function of human NK cells activated with IL-21, which signals primarily through STAT3. These IL-21-expanded NK cells also have increased NKG2D expression, which led us to focus ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 45 publications
4
67
0
Order By: Relevance
“…The surface levels of NKG2D on M1-primed NK cells also decreased after the masking of IL-23p19 (Fig. 3B), which is known to share with IL-12 some functional properties (46,47).…”
Section: M1 Macrophages Induce Nkp44 and Nkg2d Upregulation Via Il-1bmentioning
confidence: 89%
“…The surface levels of NKG2D on M1-primed NK cells also decreased after the masking of IL-23p19 (Fig. 3B), which is known to share with IL-12 some functional properties (46,47).…”
Section: M1 Macrophages Induce Nkp44 and Nkg2d Upregulation Via Il-1bmentioning
confidence: 89%
“…Zhu et al claimed that IL-21 initiated activation of STAT3, which accounts for the transcriptional induction of NKG2D expression on NK cells. 15 Inspired by this finding, we attempted to determine whether pSTAT3 is the downstream transcriptional factor for TCR and CD28 activation to induce NKG2D expression on CD8 C T cells. Given that a previous study reported that inhibition of the kinase activity of Lck Figure 8.…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al 15 found that IL-21 upregulated NKG2D expression on NK cells via phosphorylation of STAT3. In addition, STAT3 signaling is required for regulation of terminal differentiation of IgG B cells, 16 maintenance of Th17 cells, 17 and development of memory T cells.…”
Section: Introductionmentioning
confidence: 99%
“…35,36 We found lower expression of the NK cell activating receptor NKGD2 in Tyk2 ¡/¡ NK cells. Expression of NKG2D in splenic NK cells from na€ ıve mice is regulated in a STAT3-dependent, STAT1-and IFNAR1-independent manner, 40,50 suggesting a link between TYK2 and STAT3 functions. However, TYK2 deficiency did not recapitulate the increased expression of DNAM-1, GZMB and PRF1 reported in STAT3-deficient NK cells, 51 arguing against a general impairment of STAT3 activity in the absence of TYK2.…”
Section: Discussionmentioning
confidence: 99%